Strategic Director Appointments - DRYMIOTES, GEORGE; SIVARAMAKRISHNAN, KONDURU (Journal of Accounting Research, 2021)
ABSTRACT Recent corporate governance scandals have been attributed to a lack of board independence because of the influence CEOs have over their boards. However, CEOs can also affect board efficacy without compromising its independence by strategically choosing directors. We offer a theoretical framework to examine how CEOs can strategically choose director characteristics (such as expertise and skill set) to influence the inner workings of the board. We examine how director expertise affects the board's equilibrium voting strategies and show that some “passivity” on the part of directors can in fact be desirable equilibrium behavior. More importantly, we show that managers can strategically appoint independent outside directors to influence board voting in their favor. Surprisingly, contrary to what we might expect, we find that opportunistic (principled) managers may not always appoint the least (most) able directors to the board. We also examine whether CEOs would prefer a “captured” board (i.e., an insider‐dominated board) and show that the value of director input (i.e., the board's advising role) and the financial markets can discourage CEOs from pursuing such appointments.